Application of anticorrosive materials in cement slurry: Progress and prospect - Yihang Zhang; Jiaxin Wen; Xuejiao Yin; Xin Zhang (Frontiers in Materials, 2022)
During gas well cementing operation, the erosion of acidic formation corrosive medium will destroy the cementation between the cement slurry and the sidewall in the well sealing section, reduce the mechanical properties of the cement paste, cause problems such as sidewall collapse and casing damage, seriously endanger the normal exploitation of oil and gas resources, and cause major safety accidents. Therefore, improving the corrosion resistance of cement paste is the key to ensuring long-term stable cementing of high-temperature sour gas wells. This paper summarizes the influencing factors, corrosion mechanism, corrosion test methods and research status of anti-corrosion oil well cement additives, discusses the advantages and disadvantages of each anti-corrosion additive, summarizes the latest progress and challenges of anti-corrosion oil well cement, and aims to provide some reference for researchers in related fields.